Molecular Epidemiology Study of Mycobacterium Tuberculosis Complex - Shah, Yogendra (IntechOpen, 2021)
Tuberculosis (TB), which is caused by the infectious agent Mycobacterium tuberculosis (MTB), is a major global public health problem that infects one third of the world's population. This book provides an overview of the molecular epidemiology pattern, transmission dynamics, host response, evolution, and pathogenesis mechanisms of TB. Chapters explore such topics as mechanisms associated with increasing trends of drug-resistant TB, the development of anti-mycobacterial drugs, genotyping tools, diagnosis and treatment of latent tuberculosis infection, and more.